Perancangan Adaptor Tabung Conical 50 mL Berbasis 3D Printing terhadap Operasional Rotor Round bucket #7555 pada Sentrifus Sorvall Biofuge Primo - Priyanto, Ashari (Indonesian Journal of Laboratory, 2026)
ABSTRACT.Centrifugation is an essential technique in laboratory research used to separate components based on density. At the Laboratory of Food Biochemistry and Agricultural Product Chemistry, Faculty of Agricultural Technology, Universitas Gadjah Mada, the use of 50 mL conical tubes in a Thermo Scientific Sorvall Biofuge Primo centrifuge with rotor round bucket #7555 presents stability issues due to dimensional incompatibility. To address this, a custom adaptor was designed using 3D printing technology with PETG (Polyethylene Terephthalate Glycol) material, featuring a height of 75 mm, outer diameter of 46.1 mm, inner diameter of 30 mm, and a 2 mm side notch for installation flexibility. The process included digital design, material selection based on mechanical, thermal, and chemical resistance, and stability testing with variations in sample volume and rotational speed. Testing was conducted over eight days (June 2–11, 2025), with a total centrifugation time of 760 minutes. Initial sample volumes ranged from 10 to 45 mL , then standardized to 45–48 grams per tube at speeds of 2000 to 4000 rpm. Results showed that the PETG adaptor effectively maintained tube stability without excessive vibration or damage and was more durable than temporary cardboard solutions. These findings demonstrate that the PETG 3D-printed adaptor offers an effective and safe solution for using 50 mL conical tubes in incompatible centrifuge rotors.ABSTRAK.Sentrifugasi merupakan teknik penting dalam penelitian laboratorium untuk memisahkan komponen berdasarkan densitas. Di Laboratorium Kimia Biokimia Pangan dan Hasil Pertanian, Fakultas Teknologi Pertanian Universitas Gadjah Mada, penggunaan tabung conical 50 mL pada sentrifuge Thermo Scientific Sorvall Biofuge Primo dengan rotor round bucket #7555 memiliki masalah kestabilan akibat ketidaksesuaian dimensi. Untuk mengatasinya, dirancang adaptor khusus menggunakan teknologi 3D printing berbahan PETG (Polyethylene Terephthalate Glycol) dengan tinggi 75 mm, diameter luar 46,1 mm, diameter dalam 30 mm, dan coakan selebar 2 mm. Proses meliputi desain digital, pemilihan material berdasarkan ketahanan mekanik, termal, dan kimia, serta uji kestabilan dengan variasi volume larutan dan kecepatan putar. Pengujian dilakukan selama delapan hari (2–11 Juni 2025) dengan total waktu sentrifugasi 760 menit. Volume awal sampel 10–45 mL, kemudian distandarkan menjadi 45–48 gram per tabung, pada kecepatan 2000–4000 rpm. Hasil menunjukkan adaptor PETG mampu menjaga kestabilan tabung tanpa getaran berlebih atau kerusakan, serta lebih tahan lama dibandingkan solusi sementara dari kardus. Dai penelitian ini dapat disimpulkan bahwa adaptor cetak 3D berbahan PETG merupakan solusi efektif dan aman untuk penggunaan tabung conical 50 mL pada rotor sentrifuse yang tidak kompatibel.